Hydrodesulfurization plant evaluation to obtain 0.05% sulphur diesel - Jiménez, Edith; Lugo, Helí (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
A hydrodesulphurization plant which produces diesel fuel was evaluated, to determine the factibility to low the sulfur content in the product from its actual value of 0.15% to 0.05%. It was made by changing the operating conditions of the plant and the feed composition to obtain a sulphur content in the product of 0.05 weight percent required by specification. In this way the reactors, acid gas absorber, compressors, furnace and heat-exchangers were evaluated. The results let identify the limitation of the plant when it produced 0.05 weight percent suIfur diesel. In addition, the reactors of the plantcan generate a high grade desulphurizated product without reaching the catalyst temperature or equipment mechanical limitations.